PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE, LIKUIDITAS, DAN BASIS KEPEMILIKAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2012-2014 - Rindu Kurnia Putri; Zulbahridar '; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims size, profitability, laverage, liquidity, and based ownership to examine the effect of to corporate social responsibility. The sample used in this study are the mining companies listed on the Indonesian Stock Exchange (IDX) during the period 2012 to 2014 where the total sample is used by 25 companies. The sampling thecnique in which the number of observation obtained this study was 75 (25x3). The data used in this study is secondary data obtained from published financial reports in the Indonesian Stock Exchange. The method of analysis of this study using multiple regression analysis with help of softwere SPSS version 20,0. This study used classic assumption test composed of normality test, heteroskedasity test, autocorrelation test, and multi collinearity test. While hypothesis test is down with t test. The results of this study indicate that all independent variables are size, profitability, laverage, liquidity, and based ownership affect the corporate social responsibility on the level of significant (α) < 0,05. The coefficient of determination as big as 0,819 indicates that 81,9 % of the variations that occur in the corporate social responsibility is affected by size, profitability, laverage, liquidity, and based ownership while the rest of 18,1% were affected by other variabel that were not performed in this study.Keywords : Size, profitability, laverage, liquidity, and corporate social responsibility.